AB0019 The role of the il2-il21 rs6822844 polymorphism in the predisposition to the erythrocyte sedimentation rate elevation in juvenile idiopathic arthritis. (12th June 2018) - Nazarova, L.S.; Danilko, K.V.; Malievsky, V.A.; Viktorova, T.V.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disorder in paediatrics. 1 The erythrocyte sedimentation rate (ESR) is one of the key measures of the JIA activity. 2 However, in some patients, even in the active disease period, the ESR is not elevated. 3 Objectives: The aim of the study was to assess the relationship between the IL2-IL21 rs6822844 locus polymorphic variants and a predisposition to the ESR elevation in JIA patients. Methods: The study included 255 JIA patients from the Republic of Bashkortostan, Russia. The ESR was considered elevated if its value exceeded the upper limit of the normal range two or more times. Genotyping was performed by real-time PCR, statistical analysis – using the two-tailed Fisher exact test (p) and the odds ratio (OR) with a 95% confidence interval (CI). Results: The girls/boys ratio was 65.88%/34.12%. The ESR elevation in the active disease period was seen in 70.98% of patients. When studying the IL2-IL21 rs6822844 polymorphic locus, a marginal significance level was noted for the rarer occurrence of the GT genotype in patients with the elevated ESR (14.92% vs. 25.68%, p=0.049, OR=0.508, 95% CI 0.258–0.985, compared with patients with the normal ESR, respectively). After stratification according to the sex, similar differences in the GT genotype frequencies were seen and even intensified only for female JIA patients (15.38% vs. 31.37%, respectively, p=0.022, OR=0.398, 95% CI 0.180–0.897). In addition, a significant increase in the GG genotype proportion and a tendency towards a decrease in the T allele proportion were observed in girls with the elevated ESR (GG: 83.76% vs. 68.63%, p=0.038, OR=2.358, 95% CI 1.058–5.110; T: 8.55% vs. 15.69%, p=0.057, compared with girls with the normal ESR, respectively). Conclusions: In the present study, the association of the IL2-IL21 rs6822844 locus polymorphic variants with a predisposition to the ESR elevation in female JIA patients was shown. References: [1] Ravelli A, Martini A. Juvenile idiopathic arthritis. Lancet2007Mar 3;369(9563):767–78. [2] Giancane G, Consolaro A, Lanni S, Davì S, Schiappapietra B, Ravelli A. Juvenile Idiopathic Arthritis: Diagnosis and Treatment. Rheumatol Ther2016Dec;3(2):187–207. [3] Ramsay ES, Lerman MA. How to use the erythrocyte sedimentation rate in paediatrics. Arch Dis Child Educ Pract Ed. 2015Feb;100(1):30–6. Disclosure of Interest: None declared